Ciottone's disaster medicine - Ciottone, Gregory R.; Biddinger, Paul D.; Darling, Robert G.; Fares, Saleh; Keim, Mark E.; Molloy, Michael S.; Suner, Selim (Elsevier, 2016)
The most comprehensive resource of its kind, Ciottone's Disaster Medicine, 2nd Edition, thoroughly covers isolated domestic events as well as global disasters and humanitarian crises. Dr. Gregory Ciottone and more than 200 worldwide authorities share their knowledge and expertise on the preparation, assessment, and management of both natural and man-made disasters, including terrorist attacks and the threat of biological warfare. Part 1 offers an A-to-Z resource for every aspect of disaster medicine and management, while Part 2 features an exhaustive compilation of every conceivable disaster event, organized to facilitate quick reference in a real-time setting. - Resumé vydavatel
Keywords: medicína katastrof -- metody; krizový management -- metody; biologický terorismus; prevence katastrof; katastrofy; disaster medicine -- methods; crisis management -- methods; bioterrorism; prevention of disasters; disasters; kolektivní monografie; elektronické knihy; collective monographs; electronic books